2004
DOI: 10.4141/p03-206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of harvesting time on incidence of seed-borne Fusarium spp. in spring wheat in eastern Ontario

Abstract: The effect of five harvesting times on the incidence of seed-borne Fusarium spp. was examined using three spring wheat cultivars grown at two locations in eastern Ontario in 1999 and 2000. Twelve Fusarium spp. were isolated from 3831 of the 24 000 seeds, which were surface disinfected and plated onto modified potato dextrose agar. Fusarium sporotrichioides Sherb., F. graminearum Schwabe, F. poae (Peck) Wollenw., F. equiseti (Corda) Sacc., and F. avenaceum (Fr.) Sacc. were the most frequently isolated species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…These results are in agreement with Langseth and Stabbetorp (1996) who conducted a similar experiment in Norway and reported that the effects of year, location, and variety were more important than the effect of harvest date for DON concentration. The results of the present study are also similar to those reported by Xue et al (2004) for spring wheat in eastern Ontario, where a delayed harvest had no effect on DON concentration in the harvested grain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in agreement with Langseth and Stabbetorp (1996) who conducted a similar experiment in Norway and reported that the effects of year, location, and variety were more important than the effect of harvest date for DON concentration. The results of the present study are also similar to those reported by Xue et al (2004) for spring wheat in eastern Ontario, where a delayed harvest had no effect on DON concentration in the harvested grain.…”
Section: Discussionsupporting
confidence: 90%
“…in wheat in Ontario. Xue et al (2004) demonstrated that the incidence of total Fusarium spp. increased about twofold, from 9.5% in seed harvested early to 19.8% following delayed harvest.…”
mentioning
confidence: 99%
“…Similar results were obtained by Xue et al (2004), who reported about two-fold increase in the incidence of Fusarium spp. including F. graminearum after a delayed harvest.…”
Section: Discussionsupporting
confidence: 89%
“…However, the strong correlation between harvesting time and incidences of Fusarium spp. would suggest that the mycotoxin contamination in wheat may increase if harvest is delayed (Xue et al 2004). There was a significant linear relationship between DON and ZON concentrations in UK wheat during 2001 to 2008 (Edwards 2009;Edwards 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Farrer et al (2006) ont e´galement observe´des augmentations significatives du contenu en DON chez le ble´lorsque la re´colte a e´te´retarde´e de 8 a`19 jours. Cependant, d'apre`s Xue et al (2004), la concentration en DON du ble´n'est pas affecte´e significativement pour des dates de re´colte variant de tre`s haˆtive jusqu'a`tardive c'est-a`-dire du stade Zadoks 91 jusqu'au stade Zadoks 94 (Zadoks et al 1974). Ne´anmoins, la pre´sence de F. graminearum e´tait plus importante lorsque la re´colte e´tait retarde´e.…”
unclassified